Divalent Cations Increase DNA Repair Activities of Bacterial (6‐4) Photolyases1. (January 2017) - Ma, Hongju; Zhang, Fan; Ignatz, Elisabeth; Suehnel, Martin; Xue, Peng; Scheerer, Patrick; Essen, Lars Oliver; Krauß, Norbert; Lamparter, Tilman
Abstract: The (6‐4) photolyases of the FeS‐BCP group can be considered as the most ancient type among the large family of cryptochrome and photolyase flavoproteins. In contrast to other photolyases, they contain an Fe‐S cluster of unknown function, a DMRL chromophore, an interdomain loop, which could interact with DNA, and a long C‐terminal extension. We compared DNA repair and photoreduction of two members of the FeS‐BCP family, Agrobacterium fabrum PhrB and Rhodobacter sphaeroides RsCryB, with a eukaryotic (6‐4) photolyase from Ostreococcus, OsCPF, and a member of the class III CPD photolyases, PhrA from A. fabrum . We found that the low DNA repair effectivity of FeS‐BCP proteins is largely stimulated by Mg 2+ and other divalent cations, whereas no effect of divalent cations was observed in OsCPF and PhrA. The (6‐4) repair activity in the presence of Mg 2+ is comparable with the repair activities of the other two photolyases. The photoreduction, on the other hand, is negatively affected by Mg 2+ in PhrB, but stimulated by Mg 2+ in PhrA. A clear relationship of Mg 2+ dependency on DNA repair with the evolutionary position conflicts with Mg 2+ dependency of photoreduction. We discuss the Mg 2+ effect in the context of structural data and DNA binding. Abstract : The impact of Mg 2+ on DNA repair of four different photolyases. The phylogenetic tree on the left shows the major groups of photolyases and cryptochromes. Photolyases used in the study are given by colored text. The bar charts on the right show DNA turnover rates (s −1 ; logarithmic y ‐axis) for each of the four photolyases; the color code is the same as in the phylogenetic tree (blue: Agrobacterium fabrum PhrB; magenta: Rhodobacter sphaeroides CryB; green: Ostreococcus tauri CPF1; orange: Agrobacterium fabrum PhrA). In each bar chart, turnover rates without (−) and with (+) Mg 2+ are given.